Intermittent induction of LEA peptide by lactose enhances the expression of insecticidal proteins in Bacillus thuringiensis. Issue 8 (15th June 2022) - Akthar, Mahmuda; Shimokawa, Tomoko; Wu, Yinghan; Arita, Taichi; Mizuta, Kazuhiro; Isono, Yuria; Maeda, Minoru; Ikeno, Shinya
Abstract : Cry toxins from Bacillus thuringiensis (Bt) have been extensively applied in agriculture to substitute the use of chemical insecticides. We have previously reported the use of a coexpression system in which late embryogenesis abundant (LEA) peptides under the control of the lac promoter increase the expression of insecticidal proteins in Bt. The use of lactose to induce the expression of LEA peptides may be a desirable alternative to isopropyl β‐D‐thiogalactopyranoside, the most frequently used inducer for recombinant protein expression. In this study we investigated the use of lactose as an inducer for optimal protein expression. We observed enhanced insecticidal Cry protein expression by applying a simple technique based on intermittent induction, and then optimized concentration and the point of induction time from the 11 th h to the 15 th h. Our data suggest that intermittent induction of lactose might be a new technique for the enhancement of bacterial protein expression. Abstract : The late embryogenesis abundant peptide coexpression method, in which protein expression is made more efficient by coexpressing a short peptide consisting of 13 amino acids, was used to increase the expression of insecticidal proteins expressed in Bacillus thuringiensis . Late embryogenesis abundant peptide expression was induced by intermittent addition of lactose as an expression inducer to the culture medium, resulting in effective promotion of Cry protein expression.